Measurement of the effective B_s^0 -> J/ψ K_S^0 lifetime - collaboration, L; Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
This paper reports the first measurement of the effective B_s^0 -> J/ψ K_S^0 lifetime and an updated measurement of its time-integrated branching fraction. Both measurements are performed with a data sample, corresponding to an integrated luminosity of 1.0 fb^{-1} of pp collisions, recorded by the LHCb experiment in 2011 at a centre-of-mass energy of 7 TeV. The results are: tau_J/ψK_S^0 = 1.75 +/- 0.12 (stat) +/- 0.07 (syst) and BR(B_s^0 -> J/ψ K_S^0) = (1.97 +/- 0.23) X 10^{-5}. For the latter measurement, the uncertainty includes both statistical and systematic sources.